A sandwich ELISA for detecting the hemagglutinin of avian influenza A (H10N8) virus. Issue 5 (10th January 2019) - Chen, Lingling; Ruan, Feier; Liu, Mingbin; Zhou, Jianfang; Song, Wenjun; Qin, Kun
Abstract : Novel influenza A virus (H10N8) infected human with fatality in China during 2013‐2014. It is important to detect such nonprevalent subtype influenza A virus in clinic and regular surveillance in the early stage for effective control and prevention from the potential pandemic. Unavailability of convenient rapid diagnosis for this subtype virus in resources‐limited setting is an obstacle for timely recognizing human case. In the present study, a panel of mouse H10 specific monoclonal antibodies (mAbs) was generated, two of which were used to develop a sandwich enzyme‐linked immunosorbent assay (ELISA) for detecting the hemagglutinin of avian influenza A (H10N8) virus. ELISA results showed high sensitivity with the lowest detection limit of 0.5HAU/50 μL for live virus, which laid a foundation for clinic use as a promising diagnostic methodology. Highlights: A sandwich ELISA for detecting infectious H10 subtype virus and H10 protein was developed. High quality of performance was observed in testing H10 virus. The assay warrants further optimizations in order to widen its application in clinic.